Toward a new international economic order - Behrman, Jack N. (Paris : Atlantic Institute for International Affairs, 1974)
This book is on the reason for economic order, justice in the economic system and the acceptable solutions.
Includes bibliographical references.
oo 31/7/18
Loans
Keywords: International economic relations